PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DI PT X - Henry Raditya, Ignatius; Rahardja, Edy (Diponegoro Journal of Management, 2018)
This research aims to determine and analyze factors that affect PT X employee’s organizational citizenship behavior. Job satisfaction and organizational citizenship are used as dependent variables. A high level of job satisfaction and organizational commitment will affect organizational citizenship behavior and the organization goal’s will be achieved.This research uses questionnaire as the data collection method. The research’s population is all of the PT X employee which total is 875 employees. This research uses Slovin Formula to determine the samples, so the samples can be obtained using this formula are 90 employees with confidence level of 0.01. This research uses random sampling as the sampling method.  Data analysis used in this research are validity test, reliability test, classical assumption test, multiple linear analysis, determination coefficient test, F-test, and t test.According to the multiple linear analysis’ result, job satisfaction and organizational commitment has a positive and significant effect on organizational citizenship behavior partially as well as simultaneously. The adjusted R square score is 0,309, so 30,9% organizational citizenship behavior can be explained by job satisfaction and organizational commitment and the remaining 69,1% explained by other variables aside from the research.